Critical Concepts for COVID-19 Mass Vaccination Site Operations. (15th October 2023) - Goldberg, Scott A.; Callaway, David; Resnick-Ault, Daniel; Mandavia, Sujal; Martinez, Rodrigo; Bass, Michelle; Goralnick, Eric
Abstract: Mass vaccination campaigns have been used effectively to limit the impact of communicable disease on public health. However, the scale of the coronavirus disease (COVID-19) vaccination campaign is unprecedented. Mass vaccination sites consolidate resources and experience into a single entity and are essential to achieving community ("herd") immunity rapidly, efficiently, and equitably. Health care systems, local and regional public health entities, emergency medical services, and private organizations can rapidly come together to solve problems and achieve success. As medical directors at several mass vaccination sites across the United States, we describe key mass vaccination site concepts, including site selection, operational models, patient flow, inventory management, staffing, technology, reporting, medical oversight, communication, and equity. Lessons learned from experience operating a diverse group of mass vaccination sites will help inform not only sites operating during the current pandemic, but also may serve as a blueprint for future outbreaks of highly infectious communicable disease.